SOIL ATTRIBUTES IN CONVENTIONAL TILLAGE OF Coffea arabica L.: A CASE STUDY - Mota, Raquel Pinheiro da (2018)
Coffee production presents great economic and social importance. To increases coffee production and decreases the environmental impacts of its activity, it is necessary to know the soil attributes and their impacts on plant development. Therefore, due to the importance of the soil physical and chemical attributes, as well as the significance of coffee to Brazil, the objective of this study was to evaluate the physical and chemical attributes of an Oxisol planted with coffee conducted under conventional tillage system. For the purposes of analysis and interpretation of the data, the experiment was performed and interpreted in a completely randomized design, with the factorial 3 x 2, referring to three locations in the area of the coffee plantation (planting line, canopy projection, between planting lines) and two soil layers (0 - 0.2 m and 0.2 - 0.4 m), with four replications. It is concluded that no distinctions for soil porosity and total porosity was observed among soil locations, and that ‘planting line’ position showed superior concentrations of total organic carbon and mean geometric diameter of the soil aggregates.